2023
DOI: 10.2196/41227
|View full text |Cite
|
Sign up to set email alerts
|

Engagement, Retention, and Acceptability in a Digital Health Program for Atopic Dermatitis: Prospective Interventional Study

Abstract: Background Patients with atopic dermatitis can experience chronic eczema with pruritus, skin pain, sleep problems, anxiety, and other problems that reduce their quality of life (QoL). Current treatments aim to improve these symptoms and reduce inflammation, but poor treatment adherence and disease understanding are key concerns in the long-term management of atopic dermatitis. Digital therapeutics can help with these and support patients toward a healthier lifestyle to improve their overall QoL. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Currently, there are no publications on the usability, acceptability, or impact of any of these apps in patients with AD or their caregivers, resulting in an inability to compare feasibility findings using our app to other available mobile health apps for AD. The most recent studies on mobile apps for AD focused on the burden of the disease as determined by itch score, quality of sleep, and energy or stress levels and involved a small number of users that precluded assessment of the clinical significance and impact of the app [ 7 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are no publications on the usability, acceptability, or impact of any of these apps in patients with AD or their caregivers, resulting in an inability to compare feasibility findings using our app to other available mobile health apps for AD. The most recent studies on mobile apps for AD focused on the burden of the disease as determined by itch score, quality of sleep, and energy or stress levels and involved a small number of users that precluded assessment of the clinical significance and impact of the app [ 7 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review of 11 studies exploring the therapeutic adherence of mobile apps, 7 studies confirmed that use of the mobile app increased treatment adherence [ 6 ]. The use of mobile apps in AD is still uncommon, and few of these have been scientifically studied; existing studies have mainly demonstrated a given app’s feasibility and involved small numbers of users [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%